Different Methods in Learning Language Skills with Modern Technologies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Learning a new language can feel overwhelming. Methods provide tools to deal with common difficulties, such as forgetting vocabulary or understanding fast speech. Structured methods offer milestones and goals, giving learners a sense of accomplishment as they advance. In short, methods provide the framework that transforms language learning from an overwhelming task into a systematic, achievable process.